2023
DOI: 10.21873/cgp.20388
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Pathways in Peritoneal Mesothelioma Tumorigenesis

Abstract: Background/Aim: Mesotheliomas are tumors similar to, and probably derived from, mesothelial cells. They carry acquired chromosomal rearrangements, deletions affecting CDKN2A, pathogenetic polymorphisms in NF2, and fusion genes which often contain the promiscuous EWSR1, FUS, and ALK as partner genes. Here, we report the cytogenomic results on two peritoneal mesotheliomas. Materials and Methods: Both tumors were examined using G-banding with karyotyping and array comparative genomic hybridization (aCGH). One of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 89 publications
1
0
0
Order By: Relevance
“…Loss-of-heterozygosity based on the B-allele frequency methodology and single nucleotide polymorphism (SNP) (32) showed that the disomic chromosomes 6, 10, 18, and, 21 retained heterozygosity (Table I). This is consistent with previous observations that in neoplasms with near-haploid karyotypes, the disomic chromosomes are both maternal and paternal (19,(40)(41)(42)(43). aCGH also revealed that the breakpoints in both the ABL1 and BCR genes occurred in their intron 1.…”
Section: Discussionsupporting
confidence: 92%
“…Loss-of-heterozygosity based on the B-allele frequency methodology and single nucleotide polymorphism (SNP) (32) showed that the disomic chromosomes 6, 10, 18, and, 21 retained heterozygosity (Table I). This is consistent with previous observations that in neoplasms with near-haploid karyotypes, the disomic chromosomes are both maternal and paternal (19,(40)(41)(42)(43). aCGH also revealed that the breakpoints in both the ABL1 and BCR genes occurred in their intron 1.…”
Section: Discussionsupporting
confidence: 92%